ChatGPT Integration in Higher Education: Impacts on Teaching and Professional Development of University Professors - Elmedina Nikoçeviq-Kurti , Lirika Bërdynaj-Syla (Educational Process: International Journal)
Background/purpose: The integration of ChatGPT in education shows great potential, but its success depends upon educators’ technological skills, their ability to adapt to new teaching tools, and a willingness to embrace AI as part of their instructional strategies. This qualitative study investigates the integration of AI, specifically ChatGPT, into lecture and lesson planning by faculty members in Kosovo. The study examines how ChatGPT contributes to their professional development and how it influences their higher education teaching practices.